Atomic physics of relativistic high contrast laser-produced plasmas in experiments on Leopard laser facility at UNR - Safronova, A.S.; Kantsyrev, V.L.; Faenov, A.Y.; Safronova, U.I.; Wiewior, P.; Renard-Le Galloudec, N.; Esaulov, A.A.; Weller, M.E.; Stafford, A.; Wilcox, P.; Shrestha, I.; Ouart, N.D.; et al. (High Energy Density Physics, 2012)
The results of the recent experiments focused on study of x-ray radiation from multicharged plasmas irradiated by relativistic (I > 1019 W/cm2) sub-ps laser pulses on Leopard laser facility at NTF/UNR are presented. These shots were done under different experimental conditions related to laser pulse and contrast. In particular, the duration of the laser pulse was 350 fs or 0.8 ns and the contrast was varied from high (10−7) to moderate (10−5). The thin laser targets (from 4 to 750 μm) made of a broad range of materials (from Teflon to iron and molybden to tungsten and gold) were utilized. Using the x-ray diagnostics including the high-precision spectrometer with resolution R ∼ 3000 and a survey spectrometer, we have observed unique spectral features that are illustrated in this paper. Specifically, the observed L-shell spectra for Fe targets subject to high intensity lasers (∼1019 W/cm2) indicate electron beams, while at lower intensities (∼1016 W/cm2) or for Cu targets there is much less evidence for an electron beam. In addition, K-shell Mg features with dielectronic satellites from high-Rydberg states, and the new K-shell F features with dielectronic satellites including exotic transitions from hollow ions are highlighted.